Primary Aldosteronism: Clinical Characteristics of Patients with a Paradoxical Increase in P-Aldosterone in Response to Captopril Challenge Test - Grindskar, Camilla; Andreassen, Mikkel; Feltoft, Claus Larsen; Eldrup, Ebbe; Ugleholdt, Randi Kjærsgaard; Jørgensen, Niklas Rye; Mørup, Sara; Voss, Nathalie; Krogh, Jesper (Hormone and Metabolic Research, 2025)
A proportion of patients with primary aldosteronism (PA) have a paradox increasein plasma-Aldosterone (P-Aldosterone) concentration (PAC) during the Captopril Challenge Test (CCT). This study aimed to investigate if a paradoxical rise in PAC during CCT, was associated with clinical characteristics or outcomes inpatients with PA. We hypothesized that a paradoxical response to CCT is ameasure of disease severity, reflected by a higher baseline aldosterone/renin-ratio (ARR). A retrospective study of patients with PA,confirmed by CCT, who were referred for adrenal venous sampling between May 2011and August 2021 were eligible. Patients with an increase in PAC>10% frombaseline during CCT were classified as cases, while patients with 10 to 30% suppression were classified as controls. Of 167 patients referred, 116 (70%) were eligible for this study. Based on the CCT, 61/116 (53%) were classified as cases while 55/116 (47%) were classified as controls. The baseline ARR was 122 pmol/mIU (IQR: 65 to 223) for cases and 137 pmol/mIU (IQR: 65 to 223) for controls (p=0.66). Cases had lower systolic blood pressure (p=0.02) and higherpotassium levels (p=0.05) compared to controls. Complete clinical remission was obtained in 22 of 31 (71%) of the cases and 13 of 27 (48%) of the controls (p=0.03) after adrenalectomy. In conclusion, a paradoxical response to CCT wasnot associated with ARR. By contrast, patients with a paradoxical response did have lower systolic blood pressure, higher potassium levels, and markedly higher odds of full clinical remission after adrenalectomy.
Keywords: primary aldosteronism; captopril challenge test; paradoxical response; clinical remission